Gender differences in sport injury risk and types of injuries: A retrospective twelve-month study on cross-country skiers, swimmers, long-distance runners and soccer players - Ristolainen, L.; Heinonen, A.; Waller, B.; Kujala, U. M.; Kettunen, J. A. (Journal of Sports Science & Medicine, 2009)
This twelve months survey compared injury risk and injury types by genders (312 females, 262 males) in 15- to 35-year-old cross-country skiers, swimmers, long- distance runners and soccer players. More male than female athletes reported at least one acute injury (44% vs. 35%, p < 0.05), and more male than female runners reported at least one overuse injury (69% vs. 51%, p < 0.05). When the incidence of acute and overuse injuries both separately and combined was calculated per 1000 training hours, per 1000 competition hours and all exposure hours combined we found no gender differences in either of these comparisons. After adjustment for sport event males were at increased risk for posterior thigh overuse injuries compared to females (relative risk (RR) 5.8, 95% confidence interval (CI) 1.3 to 26.4, p < 0.05) while females were at increased risk for overuse injuries in the ankle compared to males (RR 3.1, 95% CI 1.0 to 9.3, p < 0.05). After adjustment for exposure time (injuries/1000 exposure hours) significance of the difference between the sexes in overuse injury to the ankle persisted (female 0.11 vs. male 0.02 injuries/1000 exposure hours, p < 0.05). Six athletes had an anterior cruciate ligament (ACL) injury, of whom four were female soccer players. After combining all reported acute and overuse ankle and knee injuries, the proportion of athletes with such injury was higher in the female compared to male soccer players (75% and 54% respectively; p < 0.05), but no difference was found in such injuries when calculated per 1000 exposure hours. In conclusion, we found some gender differences in sport-related injuries, but most of these differences seemed to be explained at least in part by differences in the amount of training.